Kenya : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper reviews economic developments in Kenya during 1990-95. Real GDP growth decelerated from 4.3 percent in 1990 to close to zero in 1992/93. Inflation accelerated from 12 percent in the 12-month period ended December 1989 to 34 percent in March 1993. The central government's budget deficit increased from 6.7 percent in 1989/90 to 11.4 percent of GDP in 1992/93. Broad money growth (M2) accelerated from 21 percent in the 12-month period ended December 1991 to 36 percent in March 1993.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet